Menjelajahi Sikap Toleransi Siswa melalui Materi Keberagaman dalam Pendidikan Kewarganegaraan - Kesa Helmalia; Syamzaimar Syamzaimar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aimed to analyze how diversity-related content in Pancasila and Civic Education (PPKn) shapes students' attitudes toward tolerance, with a particular emphasis on the role of teachers as role models. A qualitative approach with a case study design was employed to gain an in-depth understanding of learning practices and students' experiences in the classroom. Data were collected through classroom observations, in-depth interviews with teachers and students, and document analysis related to the implementation of PPKn learning. Data trustworthiness was ensured through source triangulation, method triangulation, and member checking, following the recommendations of Creswell (2014) and Lincoln and Guba (1985). The findings revealed that diversity-related learning materials enhanced students' understanding of the importance of respecting differences in ethnicity, religion, culture, and perspectives, thereby fostering openness, mutual respect, and harmonious coexistence. However, the effectiveness of learning was influenced not only by the instructional content but also by teachers' exemplary behavior in demonstrating tolerance through daily interactions. Teachers who consistently modeled inclusive attitudes played a significant role in strengthening students' internalization of tolerance values. These findings contribute to the development of character education by highlighting teachers' role modeling as a key instrument for fostering a culture of tolerance within educational settings.